DIMENSI PENDIDIKAN DALAM KISAH-KISAH AL-QUR’AN - Loeis, Wisnawati (Turats, 2015)
This article will discuss the educational dimension in the stories of the Qur'an. The Quran has many stories to tell people in advance from the prophet, apostle ornot, among them the story of the believers and unbelievers. The Qur'an has discussed these stories are not just a matter of the story, but more than that, which explains the wisdom of the stories to take advantage and life lessons that can help us to understand and interact with it in order to prepare for the provision of the afterlife , The conclusion of this article is the stories in the Qur'an are the events in the past happened in previous ummah, sometimes the story in the Qur'an told repeatedly, was intended as the importance of the lessons to be learned from the purse